Immune checkpoint inhibitor‐related haemophagocytic lymphohistiocytosis in a patient with non‐small cell lung carcinoma. Issue 4 (8th March 2023) - Oyama, Setsuko; Shirai, Tatsuya; Abe, Yukiko; Tsuchiya, Maya; Inui, Toshiya; Suhara, Kozo; Noto, Satoshi; Kamimura, Mitsuhiro
Key message: Hemophagocytic lymphohistiocytosis (HLH) has been reported as a rare complication of immune checkpoint inhibitors (ICI); however, ICI‐related HLH is a life‐threatening and comparatively late adverse event. Early diagnosis is critical, and it should be included in the differential diagnosis especially in patients with cytopenia with fever and hyperferritinaemia. Abstract : Hemophagocytic lymphohistiocytosis (HLH) is a rare complication of immune checkpoint inhibitors (ICI), and moreover, presents several weeks or months after initiation of ICI treatment making it difficult to diagnose. We present a case, in whom pancytopenia with fever and hyperferritinaemia led us to suspect HLH. Early diagnosis of ICI‐related HLH is essential for a better outcome.